Patronage Network for the 2020 Bohar Village Head Election (PILKADES) - Suyono Suyono; Bernadetta Budi Lestari; Kinanda Pandu Listanto; Jihan Aulia Salma (Universitas of Muhammadiyah Makassar, 2024)
This study describes the Implementation of the Bohar Village Head Election Patronage Network that supports the success of the victory of the elected Village Head which is understood through patronage theory that is built and developed through knowledge and skills resources, private property resources and public ownership resources. To understand this, researchers formulated two research questions. How is the patronage network built by the elected village head to win power? How does the Bohar village's political patronage network impact public services? Through a qualitative method approach with a case method approach, this study found that the victory of the power of the elected Village Head was built on personal strength, patronage relations and patrimonial politics. Local cultural values are exploited as resources for imaging the victory of the power of the Elected Village Head. The patronage network that underpinned the victory of power of the elected village head in Bohar Village which had implications for the weakening of the Village Institution. Village democracy has become hijacked under the guise of the welfare of villagers.